PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KETERAMPILAN LITERASI KRITIS SISWA KELAS V SD NEGERI 2 BEBALANG - Mei Antari, Ni Luh Mei Antari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation and determine the improvement of critical literacy skills among fifth-grade students at SD Negeri 2 Bebalang using the Project Based Learning (PjBL) model. This Classroom Action Research (CAR) was conducted in two cycles involving 17 students, covering planning, implementation, observation, and reflection stages. Data were collected through observation, critical literacy tests, and documentation. The results showed significant improvements: teacher performance from 85% to 95%, student engagement from 58.75% to 88.75%, average critical literacy scores from 61.76 to 81.29, and classical mastery from 23.53% to 82.35%. It is concluded that PjBL effectively enhances students’ critical literacy skills through active, contextual, and student-centered learning.